2.21 BILLION REASONS: Creating Safe Environments for Children - Fairholm, Judi; Singh, Gurvinder (Psyke & Logos, 2009)
»NO VIOLENCE AGAINST CHILDREN IS JUSTIFIABLE; ALL VIOLENCE AGAINST CHILDREN IS PREVENTABLE.« Violence touches everyone; it either hides behind the closed doors of homes and institutions, or it permeates every aspect of life through war and conflict. It is a daily reality for millions of people around the world, affecting all ages and both genders within every social context and nationality. Violence is a complex problem related to patterns of individual thought and behaviour that are shaped by a multitude of forces within relationships, families, communities and societies. It is a health, social, justice, legal, economic, spiritual, development, risk management, and human rights issue. Although violence impacts members in every community and society, children and youth are the most vulnerable. In every part of their lives – their homes and families, schools, institutions, workplaces and communities – children are beaten, sexually assaulted, tortured, neglected, maimed, bought and sold, and killed. Far too often the adults in their lives are the perpetrators of their pain or the »observers« and take little or no responsibility to protect them and create safe environments. The consequences are enormous – at the individual, family, community, and societal levels.